Ethnic inequalities in child stunting and feeding practices: results from surveys in thirteen countries from Latin America - Giovanna Gatica-Domínguez; Marilia Arndt Mesenburg; Aluisio J. D. Barros; Cesar G. Victora (BMC, 2020)
Abstract Background Although the prevalence of child stunting is falling in Latin America, socioeconomic inequalities persist. However, there is limited evidence on ethnic disparities. We aimed to describe ethnic inequalities of stunting and feeding practices in thirteen Latin American countries using recent nationally representative surveys. Methods We analyzed national surveys carried out since 2006. Based on self-reported ethnicity, skin color or language, children were classified into three categories: indigenous/ afrodescendant/reference group (European or mixed ancestry). Stunting was defined as height (length)-for-age < − 2 standard deviations relative to WHO standards. Family wealth was assessed through household asset indices. We compared mean length/height-for-age and prevalence of stunting among the three ethnic groups. Results Thirteen surveys had information on indigenous and seven on afrodescendants. In all countries, the average length/height-for-age was significantly lower for indigenous, and in eleven countries there were significant differences in the prevalence of stunting: the pooled crude stunting prevalence ratio between indigenous and the reference group was 1.97 (95% CI 1.89; 2.05); after adjustment for wealth and place of residence, prevalence remained higher among indigenous (PR = 1.34, 95% CI 1.28; 1.39) in eight countries. Indigenous aged 6-23 months were more likely to be breastfed, but with poor complementary feeding, particularly in terms of dietary diversity. Afrodescendants showed few differences in height, and in two countries tended to be taller compared to the reference group. Conclusions In all Latin American countries studied, indigenous tended to be shorter and afrodescendants presented few differences with relation to the reference group. In order to reach the SDG's challenge of leaving no one behind, indigenous need to be prioritized.